Quantifying the Spatiotemporal Variations of Soil Nitrogen Fixation or Absorption from Soybean, Cotton, and Maize Planted Fields to Support Sustainable Agriculture Practices - José Bofana; Raul Domingos Mussane; Rosalina Armando Tamele; Ana Cristina Costa; Barreta Savanguane; Ivans Popinsky; António F. Matusse (Nitrogen)
Sustainable agricultural practices are pivotal for environmental preservation and enhancing crop quality. Understanding soil nutrient levels is crucial in determining appropriate fertilizer application in agriculture production systems. In the 2022/23 agricultural season, an experiment that aimed to investigate the spatial distribution of nitrogen (N2) fixation or absorption in fields cultivated with diverse crops was carried out in Mozambique. Three experimental fields were established, and the following crops were used—maize (local variety), soybean (SAN-BEIB variety), and cotton (ALBAR SZ9314 variety)—each measuring 83.35 m × 30 m. A sampling grid of 13.9 m × 10 m facilitated the collection of 24 composite soil samples per field, consisting of 5 sub-samples within 12 cells, taken at a depth of 0.0–0.20 m before planting and after harvesting, totaling 12 samples per period per field. Laboratory analysis employed the Kjeldahl method to determine total soil nitrogen levels. The Inverse Distance Weighted (IDW) method was used for mapping the spatial total soil nitrogen distribution. The results revealed distinct total soil nitrogen credit and debit patterns. Variations were notable between pre-planting and post-harvest analyses in maize and cotton, showcasing high absorption and minimal fixation. Contrary to expectations, soybeans exhibited high absorption and low fixation, challenging the determination of optimal crop rotation intervals. Quantitative results identified specific total soil nitrogen debit efficiencies of approximately 1692.29 kg ha−1 in cotton and 1081.5 kg ha−1 in maize, respectively, and a credit of 459.215 kg ha−1 in soybeans. Despite discrepancies, this study serves as a foundational platform for future research. As the findings of this study advocate for continued crop rotation practices to bolster soil health and enhance nutrient utilization, it provides the first novel insights into nitrogen dynamics of global key crops in Mozambique, revealing significant variations in nitrogen fixation and absorption across different crop types and fields, which is crucial for informing tailored agricultural practices and soil fertility management strategies.